Extensive Degloving Injury Involving Left Lower Limb And Penoscrotal Skin: A Case Report - L. M. Bariar; M. H. Khan; Satendra Saxena; Q. M. Rehman (Indian Journal of Plastic Surgery)
A case of post traumatic extensive degloving injury involving left lower limb from groin to the ankle and whole of penoscrotal skin is reported, which was successfully managed by primary split thickness skin cover.